Correlation between serum leptin and its gene expression to the anthropometric measures in overweight and obese children - Eldosouky, Maha K; Abdu Allah, Azza M; AbdElmoneim, Abeer; Al-Ahmadi, Najat Saaeid (Cellular and Molecular Biology, 2018)
Obesity is a multifactor disorder with evidence supporting the role of the genetic factor in its etiology. The present study evaluates the relationship between leptin G2548A (rs7799039) and leptin receptors (Gln223Arg (rs1137101) genotyping and its leptin level and the risk of childhood obesity. This case-control study was conducted on 168 overweight and obese Saudi children and 126 non obese one served as control. Fasting insulin, leptin, blood glucose, lipid profile levels were measured. HOMA- IR, and BMI were assessed. Genotyping of leptin and leptin receptor gene variants was done by SNP real-time PCR method. GG genotype and G allele of rs1137101 were significantly higher in overweight and obese children than controls. It showed significant association with risk of obesity OR 7.1 [ 95% CI: 3.4 – 14.8] and OR 2.8 [ 95% CI: 2.0 – 4.1] respectively. Leptin level was significantly greater in patients than controls (p<0.000*) with GG and AG genotypes having the highest level of leptin when compared with another genotype in the obese group. As regards, rs7799039 AA genotype showed significant higher leptin level than other genotypes in the same group with a non-significant difference in genotypes distribution between obese and controls. rs1137101 variant of leptin receptor and fasting leptin level are correlated with overweight and obesity in Saudi children. The GG genotype of leptin receptors rs1137101 and higher serum leptin levels can be used as risk factors for childhood obesity.